2019
DOI: 10.2478/pielxxiw-2019-0029
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with the lives of elderly nursing homes residents

Abstract: Introduction. Ageing of societies is a process apparent in nearly all countries worldwide. Many families will not be able to provide care services for the elderly, the burden of care will fall mainly on public and private institutions. This puts employees of nursing homes in front of numerous challenges in order to provide seniors with improvement of their life satisfaction.Aim. The purpose of the study was to assess the life satisfaction of elderly nursing home residents in the Mazovian region and to demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In this study, the mean LSI-A score was approximately 62% of the total score. Similar to previous studies [ 50 , 51 ] on life satisfaction of older adults in NHs, the score was lower than that of elderly people in the community [ 10 ], indicating poor life satisfaction among this population.Trybusińska et al's study also showed that older adults in NHs had a lower level of life satisfaction [ 52 ]. Many factors may contribute to the decreased life satisfaction of elderly individuals, such as health status, changes in living environment, emotional satisfaction, and family relationships [ 11 , 12 ], quality of service provided by nursing home staff [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the mean LSI-A score was approximately 62% of the total score. Similar to previous studies [ 50 , 51 ] on life satisfaction of older adults in NHs, the score was lower than that of elderly people in the community [ 10 ], indicating poor life satisfaction among this population.Trybusińska et al's study also showed that older adults in NHs had a lower level of life satisfaction [ 52 ]. Many factors may contribute to the decreased life satisfaction of elderly individuals, such as health status, changes in living environment, emotional satisfaction, and family relationships [ 11 , 12 ], quality of service provided by nursing home staff [ 53 ].…”
Section: Discussionmentioning
confidence: 99%